AUDIT OF HEALTH EXPENDITURES BY SOCIAL SECURITY INSTITUTIONS IN TURKEY (Third Sector Social Economic Review, 2016)
The Social Security Institution, that is one of Turkey’s largest budgeted organizations, has the biggest share in the health expenditure financing as well. At this point, it is important to carry out audits on the health care service providers by SSI. According to data from 2014, it is observed that one sixth of health care service providers were audited on an annual basis. This case shows us that the control is poor and limited, inefficient and ineffective. The purpose of this article to reveal the importance and the characteristics of the health inspection carried out by SSI and to demonstrate the responsible units and control systems with numerical data.
Keywords: Turkey; Health Auditing; Social Security Institution (SSI)